The impact of Ukraine's participation in global value chains on the competitiveness of the national economy - Mytsenko, V. (Економічний вісник Донбасу, 2024)
The article identifies and analyses the key factors that determine the participation of Ukrainian industry in global value chains (GVCs), with a special focus on their impact on the competitiveness of the national economy in the context of globalisation. Using regression analysis, the article confirms that Ukraine's direct participation in GVCs largely depends on the volume of foreign direct investment in the manufacturing industry, as well as the impact of the number of people employed in the industrial sector and the volume of innovative products on the overall integration into GVCs. The hypothesis about the impact of industrial employment on the content of foreign added value in exports was partially confirmed. The results of the analysis emphasise the importance of developing certain sectors, such as textiles and metallurgy, which has a positive impact on employment and innovation activity. At the same time, the need to reduce dependence on imports in high-tech products was identified. Based on the conclusions obtained, the article outlines proposals for state policy, which envisage strengthening support for investment in the processing industry, stimulating innovation processes and developing the production of final products, which will help restore and ensure the competitiveness of Ukraine's economy in the international arena. У статті здійснено ідентифікацію та аналіз ключових чинників, що визначають участь української промисловості в глобальних ланцюгах створення вартості (GVCs), з особливою увагою до їхнього впливу на конкурентоспроможність національної економіки в умовах глобалізаційних процесів. За допомогою регресійного аналізу підтверджено, що пряма участь України у GVCs значною мірою залежить від обсягів прямих іноземних інвестицій у переробну промисловість, а також впливу працевлаштованих у промисловому секторі та обсягу інноваційної продукції на загальну інтеграцію у GVCs. Частково підтверджено гіпотезу щодо впливу зайнятості в промисловості на вміст іноземної доданої вартості в експорті. Результати аналізу підкреслюють важливість розвитку певних секторів, таких як текстильна промисловість та металургія, що позитивно відображається на рівні зайнятості та інноваційній активності. Водночас виявлено необхідність скорочення залежності від імпортної складової у виробах високих технологій. На основі отриманих висновків окреслено пропозиції для державної політики, що передбачають посилення підтримки інвестицій в переробну промисловість, стимулювання інноваційних процесів та розвитку виробництва кінцевої продукції, що сприятиме відновленню та забезпеченню конкурентоспроможності економіки України на міжнародній арені.